What is the role of immunotherapy in treatment of peanut allergy?. Issue 7 (July 2018) - Morris, Carl; Lang, Edith
Abstract : EVIDENCE‐BASED ANSWER : Oral or sublingual peanut immunotherapy can achieve short‐term desensitization in 60% to 80% of children and adults with peanut allergy (SOR: B, meta‐analysis of small RCTs and a single RCT). In patients continuing immunotherapy for 3 years (after an initial 44 weeks of treatment), tolerance decreases significantly, but can be maintained in responders for up to 8 weeks after discontinuing immunotherapy (SOR: B, single cohort study). Currently, immunotherapy for peanut allergy is considered investigational and is not recommended for routine use (SOR: C, expert opinion).